Relationships between individual movement, trophic position and growth of juvenile pike (Esox lucius). Issue 1 (22nd March 2017) - Nyqvist, Marina J.; Cucherousset, Julien; Gozlan, Rodolphe E.; Britton, J. Robert
Abstract: Variation in movement between individuals can have important ecological effects on populations and ecosystems, yet the factors driving differences in movement and their consequences remain poorly understood. Here, individual variability in the movements of juvenile (age 0 +  and 1 +  year) pike Esox lucius was assessed using passive integrated transponder (PIT) telemetry in off‐channel nursery areas over a 26‐ month period. Differences in the movement patterns of individuals were tested against their body sizes, ages, growth rates and trophic positions using data collected through a combination of catch‐and‐release sampling and stable isotope analyses. Results revealed that variation in movement between individuals was affected by age, with 1 +  individuals moving more than individuals of age 0 + , but not length. Individuals whose TP was low on their initial capture event moved significantly less than those with a higher initial TP. Individuals that moved more grew faster and achieved a higher final TP. These results suggest that higher activity (i.e., increased movement) increases resource acquisition that enhances growth rates, which could ultimately maximise individual performances.